(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This study examines the critical role of phonological features and phono-pragmatic elements in military discourse and their implications for oral translation theory, specifically focusing on English and Uzbek military communications. Military discourse demands precise, efficient, and unambiguous communication, making phonological accuracy paramount in both monolingual operations and cross-linguistic translation scenarios. Through comparative analysis of English and Uzbek military terminology, command structures, and communication protocols, this research reveals how phonological variations can significantly impact message transmission, comprehension, and operational effectiveness. The study employs corpus analysis of military communications, phonetic transcription of key terminology, and examination of real-world translation challenges faced by military interpreters. Findings indicate that phonological mismatches between English and Uzbek create specific vulnerabilities in military translation, particularly in high-stress operational environments where acoustic clarity and rapid comprehension are essential. The research demonstrates that traditional translation approaches focusing primarily on semantic equivalence are insufficient for military contexts.